Economics, urban planning, and food systems: from “chrematistike” to “oikonomia” toward sustainable cities - Simon, Sandrine (Frontiers in Sustainable Food Systems, 2023)
The history of cities and of urbanism has closely followed economic changes—so much so that cities have been described as microcosms of our economic systems. As heavy contributors to climate change, pollution and the generation of waste, cities have been urged to embark on a transition to progressively become more sustainable. However, while efforts are being focused on transforming urbanism to face this challenge, urbanists are not sufficiently questioning the economic barometers they rely on. In an attempt to explain that making cities sustainable cannot emerge from relying on paradigms that create un-sustainability in the first place, this article suggests that insights from alternative approaches to economics (such as ecological economics) and to urban planning (that view cities as ecosystems) could help in understanding better what a transition toward sustainable cities could mean. Since jeopardized food security emerged from the recent Covid crisis as one of the main shortcomings of our globalized economic systems, the discussion places food systems at the core of the transition toward sustainable cities. What is suggested here is that, in the current context of a post-Covid, rapidly urbanizing and fighting climate change world, urbanists might find in the “oikonomia” etymological origin of economics (i.e., economics as “the management of resources to meet the needs of the household”) a better source of inspiration than in its other etymological origin of “chrematistike” (“economics as the art of generating monetary wealth”) to contribute to the type of advances in urbanism that are urgently needed.